Hubungan Antara Hasil Pembelajaran Geografi Dengan Tingkat Pengetahuan Kesiapsiagaan Bencana Banjir Di Kelas VIII SMP N 1 Nguter Kab. Sukoharjo - Anwar, Tomi, Drs. Rubino Rubiyanto, M.Pd (2016)
Floods are the most frequent threats that disrupt the activities of education and society. This research was conducted in the village Nguter, District Nguter, Sukoharjo aimmed (1) To identify the level of knowledge of students of class VIII SMP N 1 Nguter about learning geography. (2) To identify the level of preparedness of students of class VIII SMP N 1 Nguter about flood preparedness. (3) To identify the correlation between knowledge of geography teaching good students affect student preparedness in facing flood SMP N 1 Nguter class VIII. The method used is descriptive quantitative. The study population was all students of SMP N 1 Nguter and sample amounted to 10 students with the best grades in geography lesson. data collection techniques in this study, researchers used a technique nonprobability sampling, this technique does not give pelung for each element of members of the population as nonsempel, tenik sample of researchers using sempel saturated, with the questionnaire, because sempel is when the greater number of the population used the generalization level of harm small. Requirements analysis test conducted by validity and reliability test, T test results showed that the level of preparedness of students to face floods in the high category, between 0,800 up to 1.00.